Падучая звезда - Никитин Сергей Константинович (Военная библиотека школьника, 1987)
Экземпляры: (20170523) / Инвентарный номер: 20375 / Цена: 0.85 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 62 / ББК: 84(2Рос=Рус)6